Analisis Beban Kerja Fisik dan Mental pada Karyawan Produksi Es Balok Menggunakan Metode Job Strain Index (JSI) dan Metode Nasa-TLX - Masrikan, Muhammad; Sanjaya, Krishna Tri; Kalista, Anggia; Wicaksono, Nanang; Suwardana, Hendra (IMEJ (Jurnal Teknik dan Managemen Industri), 2022)
Factory production areas have a high workload for employees. Problems that exist in the company such as workers who have the risk of physical injury from being hit by large and heavy blocks of ice that have the potential to fall on the workers' feet and musculoskeletal. Mental burden that can arise because workers have to pursue the company's production targets. The purpose of this study is to analyze the physical and mental burden on workers and how to reduce the physical workload and high mental burden on workers. The object of research taken at PT. X, there are 15 employees who produce ice blocks. The analysis was carried out using two methods, namely the Job Strain Index (JSI) method and the NASA-TLX method. The results obtained were dangerous physical loads on all loading and unloading workers and for mental loads, they found that Dwi Ahmad S had a heavy mental burden, and Adam Sunoto, Bahar Kusni, Lasujji, Rio Kiki Darno S, Bisri Mustofa, Duraji, warjono, aris widodo have a moderate mental load. Suggestions are given to the loading power of ice blocks that have dangerous physical loads and heavy or moderate mental loads, by providing suggestions for improvements to each variable assessed on the JSI and NASA-TLX methods.